2015
DOI: 10.1186/s12879-015-1137-z
|View full text |Cite
|
Sign up to set email alerts
|

High rates of unplanned interruptions from HIV care early after antiretroviral therapy initiation in Nigeria

Abstract: BackgroundUnplanned care interruption (UCI) challenges effective HIV treatment. We determined the frequency and risk factors for UCI in Nigeria.MethodsWe conducted a retrospective-cohort study of adults initiating antiretroviral therapy (ART) between January 2009 and December 2011. At censor, patients were defined as in care, UCI, or inactive. Associations between baseline factors and UCI rates were quantified using Poisson regression.ResultsAmong 2,496 patients, 44 % remained in care, 35 % had ≥1 UCI, and 21 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 43 publications
2
20
0
Order By: Relevance
“…Our recent analysis was based in Nigeria, home to the second largest number of people in the world living with HIV after South Africa [1]. In our cohort, 35% of patients had UCI, and rates were highest in the first year after starting ART [3]. This study supports our experience in the field -that patients are likely to experience many episodes of UCI over the course of their care.…”
supporting
confidence: 82%
See 3 more Smart Citations
“…Our recent analysis was based in Nigeria, home to the second largest number of people in the world living with HIV after South Africa [1]. In our cohort, 35% of patients had UCI, and rates were highest in the first year after starting ART [3]. This study supports our experience in the field -that patients are likely to experience many episodes of UCI over the course of their care.…”
supporting
confidence: 82%
“…There are many potential measures of retention, and much of the retention literature has focused on patients who are lost to follow-up, despite its limitations [2]. Loss to follow-up (LTFU), as a measure, may be conflated with other poorly ascertained outcomes including undocumented transfers of care, death, or transient care interruptions [3].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In our cohort, females were over-represented amongst AYA compared to older adults, and AYA had a higher median CD4 count at baseline than older adults. A prior analysis by our group showed that high baseline CD4 is an independent risk factor for UCI from HIV care suggesting that patients who initiate ART with higher CD4 counts may be less likely to comply with care because they do not feel “sick” (3032). In our Nigerian cohort, it is possible that the high baseline CD4 in the younger population may be accounted for by a predominance of females, who tend to be diagnosed with higher CD4 counts than males (33, 34).…”
Section: Discussionmentioning
confidence: 97%